Early-life exposures and cardiovascular disease risk among Ghanaian migrant and home populations: the RODAM study. (26th June 2020) - Boateng, Daniel; Danquah, Ina; Said-Mohamed, Rihlat; Smeeth, Liam; Nicolaou, Mary; Meeks, Karlijn; Beune, Erik; Addo, Juliet; Bahendeka, Silver; Agyei-Baffour, Peter; Mockenhaupt, Frank P.; Spranger, Joachim; et al.
Abstract: Early-life environmental and nutritional exposures are considered to contribute to the differences in cardiovascular disease (CVD) burden. Among sub-Saharan African populations, the association between markers of early-life exposures such as leg length and sitting height and CVD risk is yet to be investigated. This study assessed the association between leg length, sitting height, and estimated 10-year atherosclerotic cardiovascular disease (ASCVD) risk among Ghanaian-born populations in Europe and Ghana. We constructed sex-specific quintiles for sitting height and leg length for 3250 participants aged 40–70 years (mean age 52 years; men 39.6%; women 60.4%) in the cross-sectional multicenter Research on Diabetes and Obesity among African Migrants study. Ten-year risk of ASCVD was estimated using the Pooled Cohort Equations; risk ≥7.5% was defined as "elevated" CVD risk. Prevalence ratios (PR) were estimated to determine the associations between sitting height, leg length, and estimated 10-year ASCVD risk. For both men and women, mean sitting height and leg length were highest in Europe and lowest in rural Ghana. Sitting height was inversely associated with 10-year ASCVD risk among all women (PR for 1 standard deviation increase of sitting height: 0.75; 95% confidence interval: 0.67, 0.85). Among men, an inverse association between sitting height and 10-year ASCVD risk was significant on adjustment for study site, adult, and parental education but attenuated when further adjusted for height. No association was found between leg length and estimated 10-year ASCVD risk. Early-life and childhood exposures that influence sitting height could be the important determinants of ASCVD risk in this adult population.